Sistem Pakar Untuk Mendiagnosa Penyakit Paru-Paru dengan Menggunakan Metode Teorema Bayes - Alex Wenda; Kraugusteeliana Kraugusteeliana; Andik Adi Suryanto; Sitti Nur Alam; Karya Suhada (Universitas Budi Darma, 2023)
Health is one of the most expensive assets that no one can buy. So that health is the most important thing for every human being, which is priceless. One of the important organs in the human body that greatly affects health is the lungs. The lungs are a part of the human body that plays a role in the respiratory system. Where the respiratory system holds the main control in human life after the heart. at the time of examination of the lungs, the costs required are relatively expensive. So because of the high cost of inspection and the lack of funds owned by the community, so that in the end the community becomes hesitant to carry out an examination. To help the community in dealing with these problems, a system is needed that can help the community diagnose or find out the disease that is being experienced by the community. The system is an expert system. An expert system is a system developed by experts using technology. Expert systems need methods. The method used in this study is the Bayes Theorem. The main function of this Bayes Theorem is to calculate the probability of an event or event occurring through the basis of the effect resulting from an observation or observation. After carrying out calculations based on this method, information was obtained that 90% of patients who consulted had Lung Cancer.